DASHBOARD INFORMATION UNTUK SISTEM NILAI KINERJA DOSEN DENGAN PENDEKATAN DATA CENTRIC - Setiaji, Hari (Compiler, 2016)
Nilai Kinerja Dosen (NKD) system in higher education institutions can help managers to monitor the teacher learning activity periodically . The information generated by NKD system is limited with statistical data only and with text content only. This study observed the data output from the NKD system can be processed into more valuable information and have good information visualization. One part of this research is develop a dashboard information prototype with data-centric approach. The selection of data-centric approach for quantity and variety factors of data that are found can be visualized. This study found that interactivity and analytical factors in NKD dashboard information not quite satisfy users who are top level.